In vitro and in vivo antitumor effects of the VO-chrysin complex on a new three-dimensional osteosarcoma spheroids model and a xenograft tumor in mice - León, Ignacio Esteban (2016)
Osteosarcoma (OS) is the most common primary tumor of bone, occurring predominantly in the second decade of life. High-dose cytotoxic chemotherapy and surgical resection have improved prognosis, with long-term survival for patients with localized disease. Vanadium is an ultra-trace element that after being absorbed accumulates in bone. Besides, vanadium compounds have been studied during recent years to be considered as representative of a new class of non-platinum antitumor agents. Moreover, flavonoids are a wide family of polyphenolic compounds that display many interesting biological effects. Since coordination of ligands to metals can improve the pharmacological properties, we report herein, for the first time, the in vitro and in vivo effects of an oxidovanadium(IV) complex with the flavonoid chrysin on the new 3D human osteosarcoma and xenograft osteosarcoma mice models. The pharmacological results show that VOchrys inhibited the cell viability affecting the shape and volume of the spheroids and VOchrys suppressed MG-63 tumor growth in the nude mice without inducing toxicity and side effects. As a whole, the results presented herein demonstrate that the antitumor action of the complex was very promissory on human osteosarcoma models, whereby suggesting that VOchrys is a potentially good candidate for future use in alternative antitumor treatments.